Recognizing Teachers’ Digital Literacy Strategies to Enhance Students’ Reading Comprehension - pradita, vira; Sri Kusuma Ningsih (Institut Agama Islam Negeri Palopo, 2024)
A literature review has demonstrated that the implementation of digital literacy in the learning environment leads to significant changes in students. The purpose of this study was to analyze how teachers use digital literacy strategies in learning activities. To achieve this goal, a semi-structured qualitative study was carried out with five (female) English teachers from secondary schools through focused individual interviews. Six questions were asked during the interview and the findings were analyzed. The findings indicated that teachers engaged in diverse technology professional development to integrate digital media into classroom instruction. Some teachers faced challenges in the use of technology and sought assistance from tech-savvy colleagues. Furthermore, teachers often encountered challenges in the use of copyright which highlighted the need for accessible educational resources and support in navigating copyright issues. Finally, teachers use a blended strategy by combining the use of digital and traditional media in classroom teaching. This study will be useful for teachers and school administrators in preparing for advanced education in the era of digital transformation.